Debating 'visibility' and its effects on the effective delivery of Official Development Assistance – diagnosis, justification and possibilities. (November 2014) - Vollmer, Frank
Development cooperation has to be visible in some form to ensure domestic political support for Official Development Assistance. This explains the frequent calls for greater visibility at the headquarters level of aid agencies. However, effective development cooperation is not compatible with every form of visibility. Aid practitioners at field level in partner countries report that actions geared toward increasing the effectiveness of development cooperation become more challenging if these actions lack a certain degree of visibility. Whether aid is delivered on or off the budget of the partner country or whether aid programmes are aligned to the partner country's priorities is linked to the domestic pressure on development partners for visibility in the partner country. This paper analyses the influence of visibility on the implementation of the aid effectiveness agenda. It assesses the impact of visibility on the principles and commitments of the Paris Declaration on Aid Effectiveness (2005), the Accra Agenda for Action (2008) and the Busan Partnership Agreement for Effective Development Cooperation (2011), and presents parameters of a 'new' visibility that is conducive to the agenda.